Aid, China, and growth: evidence from a new global development finance dataset - Dreher, Axel; Fuchs, Andreas; Parks, Bradley; Strange, Austin M.; Tierney, Michael J. (American economic journal. Economic policy, 2021)
This article introduces a new dataset of official financing from China to 138 developing countries between 2000 and 2014. It investigates whether Chinese development finance affects economic growth in recipient countries. The results demonstrate that Chinese development finance boosts short-term economic growth. An additional project increases growth by between 0.41 and 1.49 percentage points 2 years after commitment, on average. While this study does not find that significant financial support from China impairs the overall effectiveness of aid from Western donors, aid from the United States tends to be more effective in countries that receive no substantial support from China.